The Moderating Effects of Institutional Framing on Authentic Leadership-Physical Asset Management Practices Relationships in Local Governments in Uganda - Obicci, Peter Adoko (Innovation Journal of Social Sciences and Economic Review, 2022)
The purpose of this study is to explore the moderating effect of institutional framing on the relationship between authentic leadership and physical asset management (PAM) practices within Local Governments (LGs) in Uganda. Given the complexities introduced by resource scarcity and toxic leadership environments, this study seeks to understand how institutional framing can influence the effectiveness of authentic leadership in managing physical assets. The study employed a cross-sectional research design, collecting quantitative data through a structured questionnaire administered to 261 employees from four selected LGs in Acoliland, mid-northern Uganda. The data were analyzed using the Statistical Package for Social Scientists (SPSS) to assess the relationships between the variables. The findings indicate a positive and significant relationship between authentic leadership and institutional framing, as well as between institutional framing and PAM practices. Notably, institutional framing was found to fully mediate the relationship between authentic leadership and PAM practices, suggesting that the effectiveness of authentic leadership in enhancing PAM practices is contingent upon the presence of positive institutional framing. In conclusion, this study highlights the critical role of institutional framing in amplifying the impact of authentic leadership on PAM practices within LGs. The findings imply that policymakers and practitioners should focus on fostering positive institutional framing to improve the management of physical assets. Future research could benefit from exploring the long-term effects of institutional framing and authentic leadership on PAM practices, possibly incorporating qualitative methods to deepen the understanding of the causal relationships among these variables. The study is the first of its kind to examine the moderating role of institutional framing on the relationship between authentic leadership and PAM in a local government setting in a developing country.